Acupuncture for cognitive impairment in type 2 diabetes mellitus: a systematic review and Bayesian network meta-analysis protocol - Hong, Kun; Gao, Juan; Hu, Li-juan; Zhou, Xiu-juan; Long, Xiao-mei; Wen, Bo-ping; Wu, Xi (Frontiers in Medicine, 2025)
BackgroundThe global prevalence of diabetes mellitus (DM) has exceeded 589 million, with the proportion of type 2 diabetes mellitus (T2DM) patients with comorbid cognitive impairment (CI) as high as 49.1%, which has a serious impact on disease management and quality of life. While acupuncture has been shown to improve cerebral glucose metabolism and synaptic plasticity, existing clinical trials are plagued by critical limitations: small sample sizes (often <100 participants) fail to detect subtle treatment effects, methodological heterogeneity in acupuncture protocols (e.g., varying acupoint selections, stimulation intensities, and treatment durations) hinders evidence synthesis, and insufficient blinding (e.g., sham acupuncture controls with low plausibility) introduces performance bias. These limitations have constrained the generalizability of findings and created a significant evidence gap in defining acupuncture’s role in diabetic cognitive impairment (DCI). The aim of this study is to assess the efficacy and safety of acupuncture for DCI through a systematic review with Bayesian network meta-analysis (NMA), addressing these methodological flaws via rigorous evidence synthesis.Methods and analysisFollowing PRISMA-NMA and STRICTA-2010 guidelines, we will systematically search 10 databases (PubMed, Cochrane Library, CNKI, etc.) from inception to 30 June 2025 and gray literature (January 1, 1995, to June 30, 2025) for randomized controlled trials (RCTs) comparing acupuncture with pharmacotherapy, sham acupuncture, or standard care. Inclusion criteria: adults (≥18 years) with T2DM and CI diagnosed via validated scales such as Montreal Cognitive Assessment (MoCA), and Mini-Mental State Examination (MMSE). Primary outcomes include cognitive function scores; secondary outcomes assess adverse events (CTCAE v5.0). The risk of bias will be evaluated using Cochrane RoB 2.0 and GRADE. Bayesian NMA will synthesize direct and indirect evidence to simultaneously assess the relative efficacy and safety of acupuncture.Expected findings and conclusionThe study will clarify the relative efficacy and safety of acupuncture in improving DCI and provide evidence-based treatment options for clinical use. The results of Bayesian analyses may support acupuncture as a low-cost, low-risk adjunctive therapy, especially for patients intolerant of conventional medications. The results of the study will fill the current evidence gap and promote the standardized use of acupuncture in the management of DCI.Systematic review registrationCRD42021275161.